2014
DOI: 10.1186/1471-2164-15-174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of response to selection with three insecticides in the dengue mosquito Aedes aegypti using mRNA sequencing

Abstract: BackgroundMosquito control programmes using chemical insecticides are increasingly threatened by the development of resistance. Such resistance can be the consequence of changes in proteins targeted by insecticides (target site mediated resistance), increased insecticide biodegradation (metabolic resistance), altered transport, sequestration or other mechanisms. As opposed to target site resistance, other mechanisms are far from being fully understood. Indeed, insecticide selection often affects a large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 67 publications
4
79
1
3
Order By: Relevance
“…For example, over-transcription in a resistant strain of An . gambiae has suggested that the cuticle plays a role in response to selection pressures resulting from insecticide treatments [114]. In our study, cytochrome P450s, gluthatione S-transferases and cuticular proteins were all under-expressed in domiciliary bugs, which should be the most exposed to insecticide treatment.…”
Section: Discussionmentioning
confidence: 53%
“…For example, over-transcription in a resistant strain of An . gambiae has suggested that the cuticle plays a role in response to selection pressures resulting from insecticide treatments [114]. In our study, cytochrome P450s, gluthatione S-transferases and cuticular proteins were all under-expressed in domiciliary bugs, which should be the most exposed to insecticide treatment.…”
Section: Discussionmentioning
confidence: 53%
“…Most were previously found significantly overtranscribed in pyrethroid resistant Ae. aegypti populations according to data publicly available in the VectorBase expression browser (https://vectorbase.org, data sets from Strode et al 2008;Marcombe et al 2009;Poupardin et al 2012;David et al 2014). The majority of CNVs observed between resistant and susceptible populations were <2.5-fold, suggesting a predominance of duplications.…”
Section: Gene Amplifications Associated With Pyrethroid Resistancementioning
confidence: 99%
“…These detoxification enzymes (e.g., microsomal p450 monooxygenases, glutathione-s-transerases and various esterases) may play an important role in the development of resistance in various other species such as Drosophila spp., Heliothis virescens, Heliocoverpa armigera, Anopholes spp. and Aedes aegypti (David et al, 2014;Scott, 1999). Pesticides can also lead to oxidative stress in the organism, and up-regulation of certain detoxification or stress-related proteins could provide a potential mechanism for protection (Abdollahi, Ranjbar, Shadnia, Nikfar, & Rezaie, 2004).…”
Section: Introductionmentioning
confidence: 99%